Pengaruh ciri-ciri personal dan ciri-ciri program latihan terhadap prestasi belajar - Siti Zuliana Md Zuki; Siti Fardaniah Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2018)
The effectiveness of training is an important aspect in the development of training. After investing a lot of money to organize a training program, the organization often wants to know about the effectiveness of training given to trainee as well as how it can gives impact to the organization. This study was conducted to evaluate the effectiveness of training tested through learning performance among trainees that undergo a transition in the Perbadanan Hal Ehwal Bekas Angkatan Tentera (PERHEBAT). In this study, personal characteristics and training program characteristics acted as the independent variables in predicting learning performance. The instrument used in this study was adapted from Trainee Characteristic Scale, Training Program Characteristic Scale and Training Effectiveness Scale by Siti Fardaniah (2013) for personal characteristics, training program characteristics and learning performance. Questionnaires to measure the dimension of training transfer for the training characteristics was adapted from the Learning Transfer System Inventory (LTSI) by Holton et al. (2000). Data obtained were analyzed using Statistical Package for Social Sciences (SPSS) version 23. The multiple linear regression analysis indicated that extrinsic orientation, self-efficacy and organizational commitment have significant influence on learning performance. Relevance of training content and learning transfer design also affecedt learning performance. Findings in this study can be used as a reference to improve training effectiveness by focusing on personal characteristics and training characteristics conducted in PERHEBAT.